2022
DOI: 10.3390/mps5030038
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantification of Bisphenol-A and 4-Tert-Octylphenol in the Live Aquaculture Feed Artemia franciscana and in Its Culture Medium Using HPLC-DAD

Abstract: Aquaculture, a mass supplier of seafood, relies on plastic materials that may contain the endocrine disruptors bisphenol-A (BPA) and tert-octylphenol (t-OCT). These pollutants present toxicity to Artemia, the live aquaculture feed, and are transferred through it to the larval stages of the cultured organisms. The purpose of this work is the development and validation of an analytical method to determine BPA and t-OCT in Artemia and their culture medium, using n-octylphenol as the internal standard. Extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…3 A Main purpose of the analyzed studies as revealed by the publications in Table S1. B Overlapped main purposes with other secondary objectives of the analyzed papers [64] or by air pollution near polycarbonate molding plants [65], bee pollen [66], mussels [67] and brine shrimp [68]. Food contamination was determined in meat samples [53], beverages [55,69,70], milk [59,63,71,72], oils [56,63], and canned food products [59,71,73] with most studies revealing that BPA could be leached from the plastic can linings, packaging, and bottles [53,55,56,71,[74][75][76].…”
Section: Temporal Distribution and Purpose Of The Selected Articlesmentioning
confidence: 99%
“…3 A Main purpose of the analyzed studies as revealed by the publications in Table S1. B Overlapped main purposes with other secondary objectives of the analyzed papers [64] or by air pollution near polycarbonate molding plants [65], bee pollen [66], mussels [67] and brine shrimp [68]. Food contamination was determined in meat samples [53], beverages [55,69,70], milk [59,63,71,72], oils [56,63], and canned food products [59,71,73] with most studies revealing that BPA could be leached from the plastic can linings, packaging, and bottles [53,55,56,71,[74][75][76].…”
Section: Temporal Distribution and Purpose Of The Selected Articlesmentioning
confidence: 99%